Attenuation Law of Stress Waves in Cracked Rock Mass under Different Confining Pressures - Xiaoming Lou; Rui Luo; Jin Yu (Advances in Civil Engineering)
Through theoretical analysis and indoor model tests, this paper explores the attenuation law of stress waves in the intact confined rock mass and cracked rock mass under different confining pressures, especially the relationship between the stress attenuation coefficient, crack width, and crack angle, respectively. The tests were carried out on a triaxial test system for deep rock mass, which supports both static and dynamic loading. The research results show that the physical attenuation of the stress wave in the intact rock mass first decreases and then increases with the increase of the confining pressure and decreases with the increase of crack width. The attenuation coefficient of stress waves in the cracked rock mass depends on the crack angle and crack width. Specifically, the coefficient is negatively correlated with crack width; under no confining pressure, the coefficient decreases with the increase of the crack angle; when the confining pressure is on a moderate level, the coefficient increases with the crack angle; when the confining pressure exceeds the uniaxial intensity by 34%, the coefficient decreases again with the increase of the crack angle. The theoretical propagation equation of stress waves at the crack, which was derived from the propagation attenuation mechanism of stress waves in the cracked rock mass, was proved feasible through the comparison against the experimental results.